Negative electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

By placing a two-layer structure of the negative electrode mixture layer on the negative electrode current collector of the nonaqueous electrolyte secondary battery, the thickness ratio is adjusted by adjusting the combination and proportion of graphite particles A and B, which solves the problem of lowering the charge and discharge cycle characteristics and improves the The battery capacity retention rate.

CN119325649APending Publication Date: 2025-01-17PANASONIC ENERGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380048035.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-06-22
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing nonaqueous electrolyte secondary batteries have problems of degradation in charge and discharge cycle characteristics, and lack of improvement measures.

Method used

The negative electrode mixture layer with a two-layer structure is arranged on the negative electrode current collector, wherein the first negative electrode mixture layer contains graphite particles A, the second negative electrode mixture layer contains graphite particles A and graphite particles B with small internal void ratio, and the two layers are adjusted The thickness ratio (T1/T2) is in the range of 0.66 or more and 4.00 or less, so that the permeability of the nonaqueous electrolyte is improved to suppress the reduction of charge and discharge cycle characteristics.

Benefits of technology

The reduction of charge and discharge cycle characteristics is effectively suppressed and the capacity retention rate of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325649A_ABST
    Figure CN119325649A_ABST
Patent Text Reader

Abstract

A negative electrode (12) for a non-aqueous electrolyte secondary battery is characterized by: having a negative electrode mixture layer (32) formed on the surface of a negative electrode current collector (30); the negative electrode mixture layer (32) has a first negative electrode mixture layer (34) disposed on the negative electrode current collector (30) and a second negative electrode mixture layer (36) disposed on the first negative electrode mixture layer (34). The first negative electrode mixture layer (34) contains graphite particles A, and the second negative electrode mixture layer (36) contains the graphite particles A and graphite particles B having a smaller internal porosity than the graphite particles A; the second negative electrode mixture layer (36) has a first region (36a) and a second region (36b) disposed on the first negative electrode mixture layer (34). The content ratio of the graphite particles B in the first region (36a) is higher than the content ratio of the graphite particles B in the second region (36b); the ratio (T1 / T2) of the thickness (T1) of the first negative electrode mixture layer (34) to the thickness (T2) of the second negative electrode mixture layer (36) is in the range from 0.66 to 4.00 (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery. Background Art

[0002] Non-aqueous electrolyte secondary batteries are widely used as secondary batteries with high energy density. Patent document 1 discloses the following technology: from the viewpoint of high capacity, the negative electrode mixture layer is set as a two-layer structure, and the porosity of the negative electrode mixture layer on the positive electrode side is increased compared with the negative electrode mixture layer on the negative electrode collector side.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2003-77463 Summary of the invention

[0006] Problems to be solved by the invention

[0007] However, Patent Document 1 does not study the charge-discharge cycle characteristics, and there is room for improvement.

[0008] Therefore, an object of the present invention is to provide a negative electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery capable of suppressing a decrease in charge and discharge cycle characteristics.

[0009] Means for solving problems

[0010] A negative electrode for a non-aqueous electrolyte secondary battery as one embodiment of the present invention is characterized in that: it has a negative electrode collector and a negative electrode mixture layer formed on the surface of the negative electrode collector; the negative electrode mixture layer has a first negative electrode mixture layer arranged on the negative electrode collector and a second negative electrode mixture layer arranged on the first negative electrode mixture layer; the first negative electrode mixture layer contains graphite particles A, and the second negative electrode mixture layer contains the graphite particles A and graphite particles B having an internal porosity smaller than that of the graphite particles A; the second negative electrode mixture layer has a first region and a second region arranged on the first negative electrode mixture layer; the content ratio of the graphite particles B in the first region is higher than the content ratio of the graphite particles in the second region; and the ratio (T1 / T2) of the thickness (T1) of the first negative electrode mixture layer to the thickness (T2) of the second negative electrode mixture layer is in the range of 0.66 or more and 4.00 or less.

[0011] A nonaqueous electrolyte secondary battery as one embodiment of the present invention is characterized by comprising the above-mentioned negative electrode for the nonaqueous electrolyte secondary battery, a positive electrode, and a nonaqueous electrolyte.

[0012] Effects of the Invention

[0013] According to one embodiment of the present invention, it is possible to suppress a decrease in charge and discharge cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment.

[0015] Figure 2 It is a cross-sectional view of a negative electrode as an example of an embodiment.

[0016] Figure 3 It is a top view of a negative electrode as an example of an embodiment.

[0017] Figure 4 is a cross-sectional view showing a particle cross section of a graphite particle.

[0018] Figure 5 It is a plan view showing another example of the second negative electrode mixture layer.

[0019] Figure 6 It is a plan view showing another example of the second negative electrode mixture layer. DETAILED DESCRIPTION

[0020] Hereinafter, an example of an embodiment will be described in detail with reference to the accompanying drawings. It should be noted that the nonaqueous electrolyte secondary battery of the present invention is not limited to the embodiment described below. In addition, the drawings referred to in the description of the embodiment are schematic diagrams.

[0021] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment. Figure 1 The non-aqueous electrolyte secondary battery 10 shown has a wound electrode body 14 in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13, a non-aqueous electrolyte, insulating plates 18 and 19 respectively arranged on the upper and lower sides of the electrode body 14, and a battery case 15 for accommodating the above components. The battery case 15 is composed of a case body 16 in a cylindrical shape with a bottom and a sealing body 17 that blocks the opening of the case body 16. It should be noted that other forms of electrode bodies such as a laminated electrode body in which a positive electrode and a negative electrode are alternately laminated with a separator can also be used instead of the wound electrode body 14. In addition, as the battery case 15, a cylindrical, square, coin-shaped, button-shaped metal outer can, a bag outer body formed by laminating a resin sheet and a metal sheet, etc. can be exemplified.

[0022] The case body 16 is, for example, a metal outer can in a bottomed cylindrical shape. A gasket 28 is provided between the case body 16 and the sealing body 17 to ensure the airtightness of the battery interior. The case body 16 has, for example, an extension portion 22 in which a part of the side surface extends inwardly and supports the sealing body 17. The extension portion 22 is preferably formed in an annular shape along the circumference of the case body 16, and supports the sealing body 17 on its upper surface.

[0023] The sealing body 17 has a structure in which a filter 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. If the internal pressure of the non-aqueous electrolyte secondary battery 10 rises due to heat caused by an internal short circuit, for example, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, and the current path between the lower valve body 24 and the upper valve body 26 is cut off. If the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.

[0024] exist Figure 1 In the non-aqueous electrolyte secondary battery 10 shown, the positive electrode lead 20 attached to the positive electrode 11 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 attached to the negative electrode 12 extends to the bottom side of the case body 16 through the outside of the insulating plate 19. The positive electrode lead 20 is connected to the bottom plate of the sealing body 17, that is, the lower surface of the filter 23, by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the filter 23, becomes the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the case body 16 by welding or the like, and the case body 16 becomes the negative terminal.

[0025] Hereinafter, each component of the nonaqueous electrolyte secondary battery 10 will be described in detail.

[0026] [negative electrode]

[0027] Figure 2 is a cross-sectional view of a negative electrode as an example of an embodiment, Figure 3 is a top view of a negative electrode as an example of an embodiment. Figure 2 and 3 The negative electrode 12 is shown as Figure 1 The electrode body 14 is in a state before being wound. In addition, in the following description, in the thickness direction ( Figure 2 In the plane direction of the negative electrode 12 orthogonal to the arrow X), the longitudinal direction of the negative electrode 12 is the first direction ( Figure 2 and Figure 3The width direction of the negative electrode 12 perpendicular to the first direction is the second direction ( Figure 3 The arrow Y2 is used to illustrate this.

[0028] like Figure 2 As shown, the negative electrode 12 includes a negative electrode current collector 30 and a negative electrode mixture layer 32 formed on the surface of the negative electrode current collector 30. The negative electrode current collector 30 can be, for example, a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, or a film of the metal disposed on the surface. The thickness of the negative electrode current collector 30 is, for example, 5 μm to 30 μm.

[0029] The negative electrode mixture layer 32 includes a first negative electrode mixture layer 34 disposed on the negative electrode current collector 30 and a second negative electrode mixture layer 36 disposed on the first negative electrode mixture layer 34. The second negative electrode mixture layer 36 includes a first region 36a and a second region 36b disposed on the first negative electrode mixture layer 34. Figure 3 As shown, the first region 36a and the second region 36b are arranged in a stripe shape in a plan view. That is, the first region 36a and the second region 36b are alternately arranged along the first direction (arrow Y1: the length direction of the negative electrode). In addition, the first region 36a and the second region 36b extend in the second direction (arrow Y2: the width direction of the negative electrode) to reach both ends of the width direction of the negative electrode 12.

[0030] The first negative electrode mixture layer 34 contains graphite particles A as a negative electrode active material. In addition, the second negative electrode mixture layer 36 contains graphite particles A as a negative electrode active material and graphite particles B having a smaller internal porosity than the graphite particles A. Furthermore, the content ratio of the graphite particles B in the first region 36a constituting the second negative electrode mixture layer 36 is higher than the content ratio of the graphite particles B in the second region 36b. In addition, the ratio (T1 / T2) of the thickness (T1) of the first negative electrode mixture layer to the thickness (T2) of the second negative electrode mixture layer is in the range of 0.66 or more and 4.00 or less. Here, the content ratio of the graphite particles B in the first region 36a is the ratio of the graphite particles B to the total mass of the graphite particles contained in the first region 36a, and the content ratio of the graphite particles B in the second region 36b is the ratio of the graphite particles B to the total mass of the graphite particles contained in the second region 36b. In addition, the internal porosity of graphite particles refers to a two-dimensional value obtained by the ratio of the area of ​​the internal voids of the graphite particles to the cross-sectional area of ​​the graphite particles. Figure 4 As shown in FIG. 1 , the internal voids of the graphite particles refer to the closed voids 42 that are not connected from the inside of the particle to the surface of the particle when observing the cross section of the graphite particle 40. Figure 4 The voids 44 in the particle interior connected to the particle surface are referred to as external voids and are not included in the internal voids. The method for measuring the internal void ratio of graphite particles will be described later.

[0031] It is presumed that: as described above, by making the content ratio of graphite particles B in the first region 36a constituting the second negative electrode mixture layer 36 higher than the content ratio of graphite particles B in the second region 36b, the non-aqueous electrolyte penetrates through the first region 36a containing more graphite particles B with a small internal porosity to the second region 36b with fewer graphite particles B with a small internal porosity, so that the permeability of the non-aqueous electrolyte to the negative electrode mixture layer is improved compared to the negative electrode mixture layer not containing graphite particles B. By containing graphite particles B with a small internal porosity, it is easy to ensure the gaps between the graphite particles even if the negative electrode is rolled when making it. Therefore, in the first region 36a containing more graphite particles B with a small internal porosity, there are more gaps between the graphite particles than in the second region 36b, so the non-aqueous electrolyte is more likely to penetrate from the first region 36a. In addition, the second region 36b with a small amount of graphite particles B having a small internal porosity is likely to be thinner than the first region 36a because the graphite particles are squeezed by rolling during the manufacture of the negative electrode, and the gaps between the graphite particles are reduced. It is speculated that since the surface of the second negative electrode mixture layer 36 is uneven, the non-aqueous electrolyte easily penetrates from the gaps generated by the unevenness, thereby improving the permeability of the non-aqueous electrolyte to the negative electrode mixture layer 32. In addition, by making the thickness ratio (T1 / T2) of the first negative electrode mixture layer 34 formed on the negative electrode collector 30 and the second negative electrode mixture layer 36 formed on the first negative electrode mixture layer 34 in the range of 0.66 or more and 4.00 or less, the effect of the permeability of the non-aqueous electrolyte brought by the above-mentioned second negative electrode mixture layer 36 can be fully exerted, and the reduction of the charge and discharge cycle characteristics of the battery can be suppressed.

[0032] The internal porosity of the graphite particles A and B was determined by the following procedure.

[0033] <Method for measuring internal void ratio>

[0034] (1) Exposing the cross section of the negative electrode active material layer. Examples of methods for exposing the cross section include cutting a portion of the negative electrode and processing it using an ion milling device (eg, IM4000PLUS manufactured by Hitachi High-Tech Corporation) to expose the cross section of the negative electrode active material layer.

[0035] (2) Using a scanning electron microscope, a backscattered electron image of the cross section of the exposed negative electrode active material layer is taken. The backscattered electron image is taken at a magnification of 3,000 to 5,000 times.

[0036] (3) The cross-sectional image obtained in the above manner is input into a computer and binarized using image analysis software (e.g., ImageJ, manufactured by the National Institutes of Health, U.S.A.) to obtain a binary processed image in which the particle cross section in the cross-sectional image is converted to black and the voids existing in the particle cross section are converted to white.

[0037] (4) Select graphite particles A and B with a particle size of 5 μm to 50 μm from the binary processed image, and calculate the area of ​​the cross section of the graphite particle and the area of ​​the internal voids existing in the cross section of the graphite particle. Here, the area of ​​the cross section of the graphite particle refers to the area of ​​the region formed by the outer periphery of the graphite particle, that is, the area of ​​the entire cross section of the graphite particle. In addition, for voids with a width of less than 3 μm in the cross section of the graphite particle, it is sometimes difficult to distinguish whether it is an internal void or an external void in image analysis, so the voids with a width of less than 3 μm can be regarded as internal voids. In addition, from the calculated area of ​​the cross section of the graphite particle and the area of ​​the internal voids in the cross section of the graphite particle, the internal void ratio of the graphite particle is calculated (area of ​​the internal voids in the cross section of the graphite particle × 100 / area of ​​the cross section of the graphite particle). The internal void ratios of the graphite particles A and B are set to the average values ​​of 10 graphite particles A and B, respectively.

[0038] The internal porosity of graphite particles A is preferably 8% to 20%, more preferably 10% to 18%, and particularly preferably 12% to 16%. As such, graphite particles A with a large internal porosity can be made, for example, as follows. The coke (precursor) as the main raw material is crushed into a specified size, and after agglomerating them with a binder, they are further fired at a temperature of 2600°C or above in a state of being pressed into a block shape to graphitize them. The block-shaped molded body after graphitization is crushed and sieved to obtain graphite particles of the desired size. Here, by increasing the amount of volatile components added to the block-shaped molded body, the internal porosity of the graphite particles can be increased (for example, in the range of 8% to 20%). In the case where a portion of the binder added to the coke (precursor) volatilizes during firing, the binder can be used as a volatile component. Asphalt can be exemplified as such a binder.

[0039] The internal porosity of graphite particles B is, for example, preferably less than 5%, more preferably 1% to 5%, and particularly preferably 3% to 5%. In this way, graphite particles with a small internal porosity can be made, for example, as follows. The coke (precursor) as the main raw material is crushed into a specified size, and in a state where they are agglomerated with a binder, they are fired at a temperature above 2600°C, graphitized, and then sieved to obtain graphite particles of the desired size. Here, the internal porosity of the graphite particles can be adjusted according to the particle size of the precursor after crushing, the particle size of the precursor in the state after agglomeration, etc. For example, by increasing the particle size of the precursor after crushing and the particle size of the precursor in the state after agglomeration, the internal porosity of the graphite particles can be reduced (for example, less than 5%).

[0040] The graphite particles A and B used in this embodiment are natural graphite, artificial graphite, etc., and are not particularly limited. However, artificial graphite is preferred from the perspective of the ease of adjusting the internal porosity. The interplanar spacing (d ) of the (002) plane of the graphite particles A and B used in this embodiment based on the wide-angle X-ray diffraction method is 002 ) is preferably 0.3354 nm or more, more preferably 0.3357 nm or more, and preferably less than 0.340 nm, more preferably 0.338 nm or less. In addition, the crystallite size (Lc (002)) of the graphite particles determined by X-ray diffraction is preferably 5 nm or more, more preferably 10 nm or more, and preferably 300 nm or less, more preferably 200 nm or less. In the interplanar spacing (d 002 When the graphite particle A and the crystallite size (Lc(002)) satisfy the above ranges, the battery capacity of the non-aqueous electrolyte secondary battery tends to be larger than when the above ranges are not satisfied. It should be noted that at least a part of the surface of the graphite particle A may be covered with amorphous carbon.

[0041] In the present embodiment, the content ratio of the graphite particles B in the first region 36a is higher than the content ratio of the graphite particles in the second region 36b. Therefore, the first region 36a may contain only the graphite particles B among the graphite particles A and B, or may contain the graphite particles A and B. In addition, the second region 36b may contain only the graphite particles A among the graphite particles A and B, or may contain the graphite particles A and B. From the viewpoint of suppressing the reduction of the charge and discharge cycle characteristics, the first region 36a preferably contains both the graphite particles A and B. In this case, the range of the mass ratio of the graphite particles A to the graphite particles B in the first region 36a is preferably, for example, in the range of 2:8 to 4:6.

[0042] The content ratio of the graphite particles B in the first region 36a is preferably, for example, 40% by mass or more and 100% by mass or less, and more preferably 60% by mass or more and 100% by mass or less, relative to the total mass of the graphite particles contained in the first region 36a, from the viewpoint of suppressing the reduction of the charge-discharge cycle characteristics. In addition, the content ratio of the graphite particles B in the second region 36b is preferably, for example, 0% by mass or more and less than 40% by mass, and more preferably 0% by mass or more and less than 20% by mass, relative to the total mass of the graphite particles contained in the second region 36b, from the viewpoint of suppressing the reduction of the charge-discharge cycle characteristics.

[0043] The first negative electrode mixture layer 34 may contain only graphite particles A or graphite particles A and B. However, from the viewpoint of improving the adhesion between the negative electrode mixture layer 32 and the negative electrode current collector 30 and further suppressing the reduction of the charge-discharge cycle characteristics, the graphite particles contained in the first negative electrode mixture layer 34 are preferably only graphite particles A. It should be noted that when the first negative electrode mixture layer 34 contains both graphite particles A and B, the mass ratio of graphite particles A to graphite particles B in the first negative electrode mixture layer 34 is preferably in the range of 7:3 to 9:1, for example, from the viewpoint of the adhesion between the negative electrode mixture layer 32 and the negative electrode current collector 30.

[0044] The ratio (T1 / T2) of the thickness (T1) of the first negative electrode mixture layer 34 to the thickness (T2) of the second negative electrode mixture layer 36 may be in the range of 0.66 to 4.00, but is preferably in the range of 1.00 to 2.50 from the viewpoint of further suppressing the reduction in charge and discharge characteristics.

[0045] The width of the first region 36a in the first direction ( Figure 3 Wx) and the width of the second region 36b in the first direction ( Figure 3 The ratio (Wx / Wy) of Wx / Wy shown in the figure is preferably, for example, 0.03 or more and 3.13 or less. When Wx / Wy satisfies the above range, the permeability of the nonaqueous electrolyte to the negative electrode mixture layer 32 is improved compared with the case where Wx / Wy does not satisfy the above range, and the reduction in the charge-discharge cycle characteristics is further suppressed.

[0046] The arrangement of the first region 36a and the second region 36b in a plan view is not limited to Figure 3 The stripes shown. Figure 5 and 6 1 is a top view showing another example of the second negative electrode mixture layer. The first region 36a and the second region 36b may be arranged, for example, as follows in a top view: Figure 5 A checkered pattern such as shown, or Figure 6 Although the illustration with the drawings is omitted, the first region 36a and the second region 36b may be arranged in a spiral shape, for example, in a plan view.

[0047] The negative electrode active material contained in the negative electrode mixture layer 32 may contain other materials capable of reversibly storing and releasing lithium ions, such as Si-based materials, in addition to the graphite particles A and B used in this embodiment. Examples of Si-based materials include Si, alloys containing Si, and SiO X (X is 0.8 to 1.6) and other silicon oxides, Li 2y SiO (2+y)Si-containing materials in which Si particles are dispersed in a lithium silicate phase as shown in (0<y<2), etc. By containing Si-based materials as negative electrode active materials, it is possible to increase the capacity of the battery. From the viewpoint of increasing the battery capacity and suppressing the reduction of the charge and discharge cycle characteristics, the content of the Si-based material is preferably 1 mass % to 10 mass %, and more preferably 3 mass % to 7 mass % relative to the total mass of the negative electrode active material contained in the negative electrode mixture layer 32.

[0048] As other materials that can reversibly store and release lithium ions, for example, Sn, alloys containing Sn, Sn-based materials such as tin oxide, Ti-based materials such as lithium titanate, etc. The negative electrode active material may contain the above-mentioned other materials, and the content of the above-mentioned other materials is preferably 10% by mass or less relative to the total mass of the negative electrode active material contained in the negative electrode mixture layer 32.

[0049] The negative electrode mixture layer 32 may contain a conductive agent. Examples of the conductive agent include carbon black (CB), acetylene black (AB), Ketjen black, graphite, carbon nanotubes and other carbon materials. These may be used alone or in combination of two or more.

[0050] The negative electrode mixture layer 32 may further include a binder. Examples of the binder include fluorine resins, polyimide resins, acrylic resins, polyolefin resins, polyacrylonitrile (PAN), styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or its salts, polyacrylic acid (PAA) or its salts (PAA-Na, PAA-K, etc., and partially neutralized salts), polyvinyl alcohol (PVA), etc. These may be used alone or in combination of two or more.

[0051] An example of a method for making the negative electrode 12 of the present embodiment is described. First, graphite particles A, a binder, and a solvent such as water are mixed to prepare a slurry for the first negative electrode mixture layer. In addition, while mixing graphite particles A and B, a binder, and a solvent such as water to prepare a slurry for the first region, graphite particles A and B, a binder, and a solvent such as water are mixed to prepare a slurry for the second region. However, the content of graphite particles B in the slurry for the first region is made greater than the content of graphite particles B in the slurry for the second region. Then, the slurry for the first negative electrode mixture layer is applied to both sides of the negative electrode collector and dried. Then, on the coating formed by the first negative electrode mixture slurry, the slurry for the first region and the slurry for the second region are alternately applied in the surface direction, and rolled using a calendering roller. Thus, the negative electrode 12 can be manufactured in which the first negative electrode mixture layer 34 is formed on the negative electrode current collector 30, and the second negative electrode mixture layer 36 having the first region 36a and the second region 36b is formed on the first negative electrode mixture layer 34. It should be noted that in the above method, the slurry for the first region and the slurry for the second region are applied after the slurry for the first negative electrode mixture layer is applied and dried, but the slurry for the first region and the slurry for the second region may be applied after the slurry for the first negative electrode mixture layer is applied and before drying. In addition, the slurry for the first region and the slurry for the second region may be applied on the first negative electrode mixture layer 34 after the slurry for the first negative electrode mixture layer is applied, dried and rolled.

[0052] [positive electrode]

[0053] The positive electrode 11 is composed of, for example, a positive electrode current collector such as a metal foil and a positive electrode mixture layer formed on the positive electrode current collector. The positive electrode current collector may be a foil of a metal such as aluminum that is stable within the potential range of the positive electrode, a film in which the metal is arranged on the surface, or the like. The positive electrode mixture layer may include, for example, a positive electrode active material, a binder, a conductive agent, and the like. The positive electrode 11 may be produced, for example, by applying a positive electrode mixture slurry including a positive electrode active material, a binder, a conductive agent, and the like on the positive electrode current collector, drying the mixture to form a positive electrode mixture layer, and then rolling the positive electrode mixture layer.

[0054] Examples of the positive electrode active material include lithium transition metal oxides containing transition metal elements such as Co, Mn, and Ni. For example, lithium transition metal oxides are Li x CoO2、Li x NiO2、Li x MnO2、Li x Co y Ni 1-y O2、Li x Co y M 1-y O z , Li x Ni 1- y My O z , Li x Mn2O4、Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (M: at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3). They can be used alone or in combination. From the perspective of achieving a high capacity of a non-aqueous electrolyte secondary battery, the positive electrode active material preferably contains Li x NiO2、Li x Co y Ni 1-y O2、Li x Ni 1-y M y O z (M: at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3) and the like lithium nickel composite oxides.

[0055] Examples of the conductive agent include carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotubes (CNT), graphene, graphite and other carbon particles, etc. These may be used alone or in combination of two or more.

[0056] Examples of the binder include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyimide-based resins, acrylic resins, polyolefin-based resins, and polyacrylonitrile (PAN), etc. These may be used alone or in combination of two or more.

[0057] [Diaphragm]

[0058] The separator 13 may be, for example, a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, and the like. Suitable materials for the separator include olefin resins such as polyethylene and polypropylene, and cellulose. The separator 13 may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. In addition, it may be a multilayer separator comprising a polyethylene layer and a polypropylene layer, or a separator having a material such as an aramid resin or ceramics coated on the surface of the separator 13 may be used.

[0059] [Non-aqueous electrolyte]

[0060] The non-aqueous electrolyte is a liquid electrolyte (electrolyte) containing a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. Examples of the non-aqueous solvent include esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more thereof. The non-aqueous solvent may contain a halogen-substituted substance in which at least a portion of the hydrogen in the solvent is replaced by a halogen atom such as fluorine.

[0061] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone and γ-valerolactone; and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.

[0062] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl Vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, ethyl benzyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and other chain ethers, etc.

[0063] As the halogen-substituted product, preferably used are fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylates such as fluoromethyl propionate (FMP), and the like.

[0064] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1<x<6, n is 1 or 2), LiB 10 Cl 10, LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, Li2B4O7, Li(B(C2O4)F2) and other borates, LiN(SO2CF3)2, LiN(C1F 2l+1 SO2) (C m F 2m+1 SO2) {l, m is an integer greater than 1} and other imide salts. The lithium salt may be used alone or in combination. Among them, LiPF6 is preferably used from the viewpoint of ion conductivity and electrochemical stability. The concentration of the lithium salt is preferably 0.8 to 1.8 mol per 1 L of solvent.

[0065] Example

[0066] Hereinafter, the present invention will be further described by way of examples, but the present invention is not limited to these examples.

[0067] <Example 1>

[0068] [Production of positive electrode]

[0069] As the positive electrode active material, LiNi 0.88 Co 0.09 Al 0.03 The lithium transition metal oxide shown. The positive electrode active material is mixed in such a manner that 100 parts by mass, carbon black as a conductive agent is 0.8 parts by mass, and polyvinylidene fluoride powder as a binder is 0.7 parts by mass, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) is further added to prepare a positive electrode mixture slurry. The slurry is applied to both sides of a positive electrode collector formed of aluminum foil (thickness 15 μm), and after the coating is dried, the coating is rolled using a calendering roll to produce a positive electrode having a positive electrode mixture layer formed on both sides of the positive electrode collector.

[0070] [Preparation of graphite particles A]

[0071] The coke was crushed to an average particle size (D50) of 15 μm, and pitch was added as a binder to the crushed coke to agglomerate the coke. Isotropic pressure was applied to the agglomerate to produce a 1.6 g / cm 3 ~1.9g / cm 3 The block-shaped compact was fired at 2800° C. to graphitize the block-shaped compact, and then the graphitized block-shaped compact was crushed and sieved to obtain graphite particles A having a volume average particle size (D50) of 23 μm.

[0072] [Preparation of graphite particles B]

[0073] The coke was crushed to an average particle size (D50) of 12 μm, and pitch was added as a binder to the crushed coke to agglomerate it until the average particle size (D50) reached 17 μm. The agglomerate was fired at 2800°C to graphitize it. Then, the block-shaped body after graphitization was crushed and sieved to obtain graphite particles B with a volume average particle size (D50) of 23 μm.

[0074] [Production of negative electrode]

[0075] The first negative electrode active material was obtained by mixing graphite particles A and SiO at a mass ratio of 95:5. 100 parts by mass of the first negative electrode active material, 1 part by mass of sodium salt of carboxymethyl cellulose (CMC-Na) and 1 part by mass of styrene-butadiene copolymer rubber (SBR) were mixed and the mixture was kneaded in water to prepare a slurry for the first negative electrode mixture layer.

[0076] A mixed graphite obtained by mixing 20 parts by mass of graphite particles A and 80 parts by mass of graphite particles B was mixed with SiO at a mass ratio of 95:5 to obtain a second negative electrode active material. 100 parts by mass of the second negative electrode active material, 1 part by mass of CMC-Na, and 1 part by mass of SBR were mixed, and the mixture was kneaded in water to prepare a slurry for the first region. In addition, graphite particles A and SiO were mixed at a mass ratio of 95:5 to obtain a third negative electrode active material. 100 parts by mass of the third negative electrode active material, 1 part by mass of sodium salt of carboxymethyl cellulose (CMC-Na), and 1 part by mass of styrene-butadiene copolymer rubber (SBR) were mixed, and the mixture was kneaded in water to prepare a slurry for the second region.

[0077] The first negative electrode mixture layer is coated with a slurry on both sides of a negative electrode collector formed of copper foil, and dried to form the first negative electrode mixture layer. Furthermore, the above-mentioned first region slurry and second region slurry are alternately and repeatedly coated on the first negative electrode mixture layer (i.e., coated in a stripe shape) and dried to form a second negative electrode mixture layer formed by a first region and a second region having a width (Wx) and (Wy) ratio of 1:1 in the second direction. The first negative electrode mixture layer and the second negative electrode mixture layer are rolled by a rolling roller to produce a negative electrode. The ratio of the thickness of the first negative electrode mixture layer (T1) to the second negative electrode mixture layer (T2) of the produced negative electrode is 5:5.

[0078] The internal porosity of the graphite particles A and B in the negative electrode mixture layer was measured in the obtained negative electrode, and the internal porosity of the graphite particles A was 15%, and the internal porosity of the graphite particles B was 3%. The method for measuring the internal porosity is as described above.

[0079] [Preparation of non-aqueous electrolyte]

[0080] 2 parts by mass of vinylene carbonate (VC) was added to a non-aqueous solvent in which ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl carbonate (EMC) were mixed in a volume ratio of 2:6:2, and LiPF6 as an electrolyte was dissolved at a concentration of 1.3 mol / L. In this way, a non-aqueous electrolyte was prepared.

[0081] [Production of test batteries]

[0082] A positive electrode lead made of aluminum was installed on the positive electrode collector, and a negative electrode lead made of nickel was installed on the negative electrode collector, and a laminated electrode body was prepared by laminating the positive electrode and the negative electrode via a polyolefin separator. The electrode body was housed in an outer casing composed of an aluminum laminate sheet, and the above-mentioned nonaqueous electrolyte was injected, and the opening of the outer casing was sealed to obtain a test battery.

[0083] <Example 2>

[0084] A test cell was prepared in the same manner as in Example 1 except that the thickness ratio of the first negative electrode mixture layer ( T1 ) to the second negative electrode mixture layer ( T2 ) of the negative electrode was changed to 7:3.

[0085] <Example 3>

[0086] A test cell was prepared in the same manner as in Example 1 except that the thickness ratio of the first negative electrode mixture layer ( T1 ) to the second negative electrode mixture layer ( T2 ) of the negative electrode was 8:2.

[0087] <Example 4>

[0088] A test cell was produced in the same manner as in Example 1, except that a second negative electrode active material was used in which a mixed graphite obtained by mixing 40 parts by mass of graphite particles A and 60 parts by mass of graphite particles B and SiO were mixed in a mass ratio of 95:5. In the preparation of the slurry for the first region, a third negative electrode active material was used in which a mixed graphite obtained by mixing 80 parts by mass of graphite particles A and 20 parts by mass of graphite particles B and SiO were mixed in a mass ratio of 95:5.

[0089] <Example 5>

[0090] A test cell was prepared in the same manner as in Example 1 except that the thickness ratio of the first negative electrode mixture layer ( T1 ) to the second negative electrode mixture layer ( T2 ) of the negative electrode was 4:6.

[0091] <Comparative Example 1>

[0092] A test cell was prepared in the same manner as in Example 1 except that the thickness ratio of the first negative electrode mixture layer ( T1 ) to the second negative electrode mixture layer ( T2 ) of the negative electrode was 9:1.

[0093] <Comparative Example 2>

[0094] A test cell was prepared in the same manner as in Example 1 except that the thickness ratio of the first negative electrode mixture layer ( T1 ) to the second negative electrode mixture layer ( T2 ) of the negative electrode was 2:8.

[0095] <Comparative Example 3>

[0096] A test cell was produced in the same manner as in Example 1, except that a second negative electrode active material was used in which a mixed graphite obtained by mixing 60 parts by mass of graphite particles A and 40 parts by mass of graphite particles B and SiO were mixed in a mass ratio of 95:5. In the preparation of the slurry for the first region, a third negative electrode active material was used in which a mixed graphite obtained by mixing 60 parts by mass of graphite particles A and 40 parts by mass of graphite particles B and SiO were mixed in a mass ratio of 95:5.

[0097] <Comparative Example 4>

[0098] A test cell was prepared in the same manner as in Example 1, except that the second negative electrode mixture layer was formed directly on the negative electrode current collector instead of forming the first negative electrode mixture layer.

[0099] [Evaluation of capacity retention rate]

[0100] At an ambient temperature of 25°C, the test battery of each embodiment and each comparative example was charged to 4.2V at a constant current of 1C, and then charged to 1 / 50C at a constant voltage of 4.2V. Then, it was discharged to 2.5V at a constant current of 0.5C. This charge and discharge was regarded as one cycle, and 200 cycles were performed. The capacity retention rate of the test battery of each embodiment and each comparative example in the charge and discharge cycle was calculated by the following formula.

[0101] Capacity retention rate = (discharge capacity at the 200th cycle / discharge capacity at the 1st cycle) × 100

[0102] Table 1 summarizes the results of the capacity retention rates of the test batteries of the respective Examples and Comparative Examples.

[0103] [Table 1]

[0104]

[0105] The test cells of Examples 1 to 5 all showed improved capacity retention rates compared to the test cells of Comparative Examples 1 to 4. Therefore, as in the test cells of the examples, the content ratio of the graphite particles B having a small internal porosity contained in the second negative electrode mixture layer is made higher in the first region than in the second region, and the thickness (T2) of the second negative electrode mixture layer and the thickness (T1) of the first negative electrode mixture layer between the second negative electrode mixture layer and the negative electrode current collector is made such that T1 / T2 is in the range of 0.66 or more and 4.00 or less, thereby suppressing the reduction in charge and discharge cycle characteristics.

[0106] <Remarks>

[0107] (1) A negative electrode for a non-aqueous electrolyte secondary battery, comprising a negative electrode current collector and a negative electrode mixture layer formed on a surface of the negative electrode current collector.

[0108] The negative electrode mixture layer includes a first negative electrode mixture layer disposed on the negative electrode current collector and a second negative electrode mixture layer disposed on the first negative electrode mixture layer.

[0109] The first negative electrode mixture layer contains graphite particles A, and the second negative electrode mixture layer contains the graphite particles A and graphite particles B having a smaller internal porosity than the graphite particles A.

[0110] The second negative electrode mixture layer has a first region and a second region disposed on the first negative electrode mixture layer, the content ratio of the graphite particles B in the first region is higher than the content ratio of the graphite particles in the second region,

[0111] A ratio ( T1 / T2 ) of the thickness ( T1 ) of the first negative electrode mixture layer to the thickness ( T2 ) of the second negative electrode mixture layer is in a range of 0.66 to 4.00. (2)

[0113] The negative electrode for a non-aqueous electrolyte secondary battery according to (1), wherein

[0114] The internal porosity of the graphite particles A is greater than 8% and less than 20%, and the internal porosity of the graphite particles B is less than 5%. (3)

[0116] The negative electrode for a non-aqueous electrolyte secondary battery according to (1) or (2), wherein:

[0117] The content ratio of the graphite particles B in the first region is greater than 40 mass % and less than 100 mass % relative to the total mass of the graphite particles contained in the first region, and the content ratio of the graphite particles B in the second region is greater than 0 mass % and less than 40 mass % relative to the total mass of the graphite particles contained in the second region. (4)

[0119] The negative electrode for a non-aqueous electrolyte secondary battery according to any one of (1) to (3), wherein

[0120] The first region and the second region are arranged in a stripe shape, a grid shape, or a honeycomb shape in a plan view. (5)

[0122] The negative electrode for a non-aqueous electrolyte secondary battery according to any one of (1) to (4), wherein

[0123] A ratio ( S1 / S2 ) of the thickness ( S1 ) of the first region to the thickness ( S2 ) of the second region is greater than or equal to 1.0 and less than or equal to 1.2. (6)

[0125] The negative electrode for a non-aqueous electrolyte secondary battery according to any one of (1) to (5), wherein:

[0126] The negative electrode mixture layer contains Si-based materials. (7)

[0128] A non-aqueous electrolyte secondary battery comprises the negative electrode for a non-aqueous electrolyte secondary battery according to any one of (1) to (6), a positive electrode, and a non-aqueous electrolyte.

[0129] Description of Reference Numerals

[0130] 10: non-aqueous electrolyte secondary battery, 11: positive electrode, 12: negative electrode, 13: separator, 14: electrode body, 15: battery case, 16: case body, 17: sealing body, 18, 19: insulating plate, 20: positive electrode lead, 21: negative electrode lead, 22: extension, 23: filter, 24: lower valve body, 25: insulating member, 26: upper valve body, 27: cover, 28: gasket, 30: negative electrode collector, 32: negative electrode mixture layer, 34: first negative electrode mixture layer, 36: second negative electrode mixture layer, 36a: first region, 36b: second region, 40: graphite particles, 42, 44: voids.

Claims

1. A negative electrode for a non-aqueous electrolyte secondary battery, comprising a negative electrode current collector and a negative electrode mixture layer formed on a surface of the negative electrode current collector, The negative electrode mixture layer includes a first negative electrode mixture layer disposed on the negative electrode current collector and a second negative electrode mixture layer disposed on the first negative electrode mixture layer. The first negative electrode mixture layer contains graphite particles A, and the second negative electrode mixture layer contains the graphite particles A and graphite particles B having a smaller internal porosity than the graphite particles A. The second negative electrode mixture layer has a first region and a second region disposed on the first negative electrode mixture layer, the content ratio of the graphite particles B in the first region is higher than the content ratio of the graphite particles in the second region, A ratio T1 / T2 of the thickness T1 of the first negative electrode mixture layer to the thickness T2 of the second negative electrode mixture layer is in a range of 0.66 to 4.

00.

2. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein The internal porosity of the graphite particles A is greater than 8% and less than 20%, and the internal porosity of the graphite particles B is less than 5%.

3. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein The content ratio of the graphite particles B in the first region is greater than 40 mass % and less than 100 mass % relative to the total mass of the graphite particles contained in the first region, and the content ratio of the graphite particles B in the second region is greater than 0 mass % and less than 40 mass % relative to the total mass of the graphite particles contained in the second region.

4. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein The first region and the second region are arranged in a stripe shape, a grid shape, or a honeycomb shape in a plan view.

5. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein The negative electrode mixture layer contains Si-based materials. 6 . A non-aqueous electrolyte secondary battery comprising the negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 , a positive electrode, and a non-aqueous electrolyte.

Citation Information

Patent Citations

  • Lithium secondary battery and its manufacturing method

    JP2003077463A